The Optimization Design of Lathe Motorized Spindle - Qiang, He; Li-Li, Li; Giron-Palomares, Benjamin; Yong, Zhang; An-Ling, Li (Recent Patents on Mechanical Engineering, 2015)
Some factors affecting the high-speed lathe motorized spindle optimal machining performance are: the big deformation of the spindle front-end, the poor cooling and heat dissipation, and the low processing precision. In this paper, first, a review is performed about recent patents on the structure design of motorized spindles and on the measurement and analysis of vibration and noise generated by motorized spindle operation. Second, an investigation is developed about an optimal design of the spindle system based on the theory of finite element optimization design and taking into account front-end overhanging volume, rotor position, and bearing span. Third, based on the theory of heat transfer and fluid dynamics, the performance of three cooling water channel geometries (annular, single spiral and double spiral) is investigated. Finally and accordingly to the three previous steps, a motorized spindle prototype is produced and tested corroborating that experimental values for temperatures at critical motorized spindle hot sources disagreed with those temperatures for a numerical model by less than 1%. Moreover, the vibration and the noise generated by the operation of this spindle prototype satisfy the Chinese national standards for motorized equipment.
Keywords: Cooling water channel